Prometeo, the grill and migration: Analysis of the Ecuadorian films Prometeo Deportado and Cesar ́s Grill - Paz-y-Miño Cepeda, Isabel (Universidade de São Paulo - Programa de Pós-graduação em Integração da América Latina, 2018)
The economic crisis in Ecuador which took place in 1999, caused the migration abroad of three million citizens. That massive exodus has been the largest in the history of this Latin American country. This article explores the consequences of migration seen from the cinematographic art. It analyzes two films by Ecuadorian directors: the fiction Prometeo deportado, by Fernando Mieles, made in 2010, that tells the story of a group of Ecuadorians locked in a room in a European airport, waiting to be deported; and the documentary El grill de César (Cesar's grill), by Darío Aguirre, produced in 2013, which recounts the return to the country of the migrant son and the reunion with his father. Beyond the studies and the data that can be cited about the most significant social problem for Ecuador in the initial decade of the 21st century, it is through art, and in this specific case through films, how it is possible to "feel" what the migration drama represents for this country.